Hacia Una Salud: estudio descriptivo de los principales agentes bacterianos de otitis externa y su susceptibilidad a los antimicrobianos, en caninos de la ciudad de Córdoba, Argentina - Ruiz, S.E. (2020)
The inadequate handling of antimicrobial drugs for its use in animals has a direct impact on the increased germs resistance, a well known current issue in public health. To count on local epidemiological data is important to guide initial empirical treatments and create surveillance plans. The objective of the present study was to know local data of the microorganisms involved in external canine otitis and their sensitivity to antimicrobial drugs. The samples (76) were collected from the exudates that were in the horizontal portion of the ear canal of dogs with characteristic symptoms of otitis. The samples were processed in a specialized laboratory in Ciudad de Córdoba, from January 2018 to December 2019. The positivity percentage was 72 %. The isolated microorganisms were Staphylococcus grupo intermedius (SGI) (36 %), Malassezia spp. (27 %), Pseudomonas aeruginosa (15 %), streptococcus beta hemolytic (9 %), Proteus mirabilis (7 %), Escherichia coli (5 %) and Enterococcus faecium (1 %). The 29 % of the SGI isolations were methicillin resistant. 26% of SGI presented multiresistance.